2004
DOI: 10.1063/1.1686905
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen lone-pair states near the valence band edge of aluminum oxide thin films

Abstract: Deep level transient spectroscopy and optical absorption spectroscopy measurement revealed three outstanding features of density-of-states ͑DOS͒ appeared above the valence band edge (E v) of Al oxide thin films. The broad peak located at 0.39 eV above E v disappears while the other two located at 1.0 and 1.3 eV shift in position and attenuate in intensity upon annealing at 200°C. The latter two peaks are removed by annealing at temperature up to 400°C. The observed midgap DOS feature dynamics is in accordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The states at the bottom of the VB are of σ g -character, whereas the states at the top of the VB display π g -character. States at the top of the VB have also been reported for the split O-interstitial in α-Al 2 O 3 (31) and were in a recent experimental study suggested to originate in coordination imperfection (7). The high energy occupied states are however not purely π g -like, but contain some contribution from all three p-orbitals of different angular momentum projection.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The states at the bottom of the VB are of σ g -character, whereas the states at the top of the VB display π g -character. States at the top of the VB have also been reported for the split O-interstitial in α-Al 2 O 3 (31) and were in a recent experimental study suggested to originate in coordination imperfection (7). The high energy occupied states are however not purely π g -like, but contain some contribution from all three p-orbitals of different angular momentum projection.…”
Section: Resultsmentioning
confidence: 74%
“…General features of the electronic structure of amorphous semiconductors are quite well known, such as the broad distribution of coordinations and the lack of long range order that induces valence and conduction band tails in the band gap (6). However, the origin of these states is less explored experimentally (7,8) and theoretical investigations are mainly limited to the crystalline polymorphs (9-11). Amorphous Alumina (am-Al 2 O 3 ) is currently one of the key technological amorphous materials, where one promising application of am-Al 2 O 3 is as a high-k dielectric in transistors (12).…”
mentioning
confidence: 99%
“…191 cm À1 ) observed in the Raman spectrum may also be attributed to the vibration of lone-pair induced dipoles of Al 2 O 3 , which is similar to that observed in posttransition metal oxides [17,18]. The non-bonding lone-pair feature of aluminum oxide has also been confirmed by deep-level transient spectroscopy method [19]. Generally, aluminum oxide exists in several crystalline phases.…”
Section: Coating Characterizationmentioning
confidence: 69%
“…[10] These defects could give rise to hole traps near the valence band edge, which could result in weak spots for tunnelling. These oxygen vacancies could be paramagnetic, which could affect spinpolarized tunnelling.…”
mentioning
confidence: 99%